Nicotinic alteration of decision-making. (September 2015) - Naudé, Jérémie; Dongelmans, Malou; Faure, Philippe
Abstract: Addiction to nicotine is characterized by impulses, urges and lack of self-control towards cigarettes. A key element in the process of addiction is the development of habits oriented towards nicotine consumption that surpass flexible systems as a consequence of a gradual adaptation to chronic drug exposure. However, the long-term effects of nicotine on brain circuits also induce wide changes in decision-making processes, affecting behaviors unrelated to cigarettes. This review aims at providing an update on the implications of nicotine on general decision-making processes, with an emphasis on impulsivity and risk-taking. As impulsivity is a rather ambiguous behavioral trait, we build on economic and normative theories to better characterize these nicotine-induced alterations in decision-making. Nonetheless, experimental data are sparse and often contradictory. We will discuss how the latest findings on the neurobiological basis of choice behavior may help disentangling these issues. We focus on the role of nicotine acetylcholine receptors and their different subunits, and on the spatio-temporal dynamics (i.e. diversity of the neural circuits, short- and long-term effects) of both endogenous acetylcholine and nicotine action. Finally, we try to link these neurobiological results with neuro-computational models of attention, valuation and action, and of the role of acetylcholine in these decision processes. This article is part of the Special Issue entitled 'The Nicotinic Acetylcholine Receptor: From Molecular Biology to Cognition'. Highlights: Nicotine impacts general decision-making processes. We focus here on impulsivity and risk taking. These effects can be described using economic and computational theories. Nicotine affects delay or probability discounting, and reward sensitivity. Nicotine effects arise from its wide neuromodulatory action on neural dynamics.